1999
DOI: 10.1038/sj.onc.1202537
|View full text |Cite
|
Sign up to set email alerts
|

A mutant form of the rho protein can restore stress fibers and adhesion plaques in v-src transformed fibroblasts

Abstract: The organization of polymerized actin in the mammalian cell is regulated by several members of the rho family. Three rho proteins, cdc42, rac and rho act in a cascade to organize the intracellular actin cytoskeleton. Rho proteins are involved in the formation of actin stress ®bers and adhesion plaques in ®broblasts. During transformation of mammalian cells by oncogenes the cytoskeleton is rearranged and stress ®bers and adhesion plaques are disintegrated. In this paper we investigate the function of the rho pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Consistent with our findings, v-Src inhibited cofilin phosphorylation and the mechanism involved a MEK-dependent and PI3 kinase-independent pathway (Pawlak and Helfman, 2002). Rho mutants restore stress fiber formation in v-Src-transformed cells (Mayer et al, 1999), consistent with a model in which Rho proteins serve as downstream targets of v-Src. In our studies, c-Jun reintroduction into c-jun Ϫ/Ϫ cells inhibited Rho kinase activity and induced cellular migration.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with our findings, v-Src inhibited cofilin phosphorylation and the mechanism involved a MEK-dependent and PI3 kinase-independent pathway (Pawlak and Helfman, 2002). Rho mutants restore stress fiber formation in v-Src-transformed cells (Mayer et al, 1999), consistent with a model in which Rho proteins serve as downstream targets of v-Src. In our studies, c-Jun reintroduction into c-jun Ϫ/Ϫ cells inhibited Rho kinase activity and induced cellular migration.…”
Section: Discussionsupporting
confidence: 78%
“…Transfection efficiency was about 50%. Reprobing the blot with an anti-EE epitope antibody confirmed that the EE-tagged RhoA proteins migrate with a higher apparent molecular weight than endogenous RhoA (not shown); the 63L and V14 point mutations are known to alter the migration of RhoA differently (73). The data in a and c are the means Ϯ S.D.…”
Section: Rho Activation In Nih 3t3 Ltr-h-ras(a) Cells and Nih 3t3 Celmentioning
confidence: 97%
“…Activated Rho can restore actin ®lament organization in Src-transformed cells (Mayer et al, 1999), and cSrc activation requires the inactivation of Rho, by enhancing GTPase activity, to induce actin ®lament dissolution (Fincham et al, 1999). GFP-AFAP-110 Dlzip was co-expressed in C3H10T1/2 cells with dominant positive Rho (RhoA V14 ) to determine if GFP-AFAP-110 Dlzip may exert its a ects on actin ®laments in a Rho-dependent fashion.…”
Section: Afap-110 Dlzip Alters Actin Filaments In a Rho-dependent Fasmentioning
confidence: 99%